"Better pathways of Care": Suggested Improvements to the Emergency Department management of People with Advanced Cancer. Issue 2 (June 2014) - Jelinek, George A.; Boughey, Mark; Marck, Claudia H.; Phillip, Jennifer; Weil, Jennifer; Lane, Heather; Weiland, Tracey J.
Objective: It is difficult to provide optimal care to people with advanced cancer presenting to emergency departments (EDs). Recent data suggest that the ED environment, the skills and priorities of treating staff, and the lack of clear communication related to goals of care contribute to the difficulty. By exploring the views of emergency, palliative care (PC), and oncology clinicians on the care of these patients, this study aimed to describe potential solutions. Methods: This qualitative study involved focus groups with clinicians at two major hospitals and two community PC services in Melbourne, Australia, and semi-structured telephone interviews with emergency clinicians from all other Australian states and territories. Discussions were recorded and transcribed verbatim. Thematic analysis identified ways to improve or enhance care. Results: Throughout discussions with 94 clinicians, a number of possible improvements to care were raised; these were broadly grouped into service areas: clinical care, pathways, information access, and education. Conclusion: The provision of care to patients with advanced cancer in the ED occurs across sites, across disciplines, and across teams. To make improvements to care, we must address these complexities. The improvements suggested in this study place the patient (and the patient's family) at the centre of care.